2012
DOI: 10.1371/journal.pone.0034713
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of UCHL1 Modulation on Alpha-Synuclein in PD-Like Models of Alpha-Synucleinopathy

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder caused by genetic and environmental factors. Abnormal accumulation and aggregation of alpha-synuclein (a-syn) within neurons, and mutations in the a-syn and UCH-L1 genes have been shown to play a role in the pathogenesis of PD. In light of recent reports suggesting an interaction between a-synuclein and UCH-L1, we investigated the effects of UCH-L1 inhibition on a-syn distribution and expression levels in primary neurons and hippocampal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 60 publications
(96 reference statements)
1
44
0
Order By: Relevance
“…Since UCHL1 inhibition increases cytoplasmic alpha-synuclein levels (Cartier et al, 2012), UCHL1 mutation might interfere with vesicular catecholamine storage in a manner similar to that in PARK1 and PARK4.…”
Section: The Catecholaldehyde Hypothesismentioning
confidence: 99%
“…Since UCHL1 inhibition increases cytoplasmic alpha-synuclein levels (Cartier et al, 2012), UCHL1 mutation might interfere with vesicular catecholamine storage in a manner similar to that in PARK1 and PARK4.…”
Section: The Catecholaldehyde Hypothesismentioning
confidence: 99%
“…LDN is a reversible, competitive, isatin derivative that selectively inhibits UCHL1 hydrolase activity (IC 50 = 0.88 μM) over a closely related DUB, UCHL3 (IC 50 = 25 μM) [35]. Although no data is available on the pharmacokinetics of LDN in mice, LDN and other isatins readily cross the blood-brain barrier [30, 36, 37], Previous work suggests that LDN is capable of exerting an inhibitory effect on UCHL1 in the hippocampus at systemic doses of 0.5 mg/kg [30, 36]; we used this reported effective dose to assess the inhibitory effect of LDN.…”
Section: Resultsmentioning
confidence: 99%
“…LDN at 1 h, 4 h, 8 h and 24 h prior to sacrifice, and levels of free monomeric ubiquitin were assessed by Western blotting, as a measure of UCHL1 inhibition [36]. These data suggested that the LDN-induced downregulation of free ubiquitin was maximal at 4 h following UCHL1 inhibition, though the effect was not significant ( P = 0.1419, Figures 5a and 5c).…”
Section: Resultsmentioning
confidence: 99%
“…Parkin-mediated α-synuclein degradation via the ubiquitin-proteasome pathway now appears unlikely, and mounting evidence suggests that α-synuclein is cleared via autophagy [60,69,88,89]. Changes in autophagy are widely recognized in neurodegeneration [90,91,92,93,94,95].…”
Section: Parkin Beyond Pd-linked Mutationsmentioning
confidence: 99%